Epistolae Iapanicae: The Letters of the First Portuguese Jesuits in Japan - Mendes de Moraes, Carlos Eduardo [UNESP]; Rodrigues Coelho, Amanda Mimoso [UNESP]; Beccari, Alessandro Jocelito [UNESP] (Univ Fed Minas Gerais, Dept Filosofia & Ciencias Humanas, 2019)
The Japanese Letters (Epistolae Iapanicae) are documents which record the activity of the Portuguese Jesuits in Japanese territory from 1549. These letters were intended to report to the crown the actions (and consequently the difficulties) of missions sent to the East, both in terms of conducting catechization and conversion, which were the main purposes for promoting the expansion of the Catholic religion, but which brought with it other intentions, such as economic and political advantages taken of that population. The work under study results from the gathering of the most significant letters sent to Portugal. Originally written in Portuguese, they were later translated into Neo-Latin, under the title Epistolae Iapanicae, de multorum gentilium in variis insulis ad Christi fidem per societatis nominis Iesu Theologos conuersione. These letters were edited in this format in 1569 by editor Ruitger Velpius (1540-1615), at the University of Leuven, with prologues and subtitles by Hannardus Gameren Mosaeus (1530-1569), sponsored by Alberto V, Duke of Bavaria (1528-1579). The purpose of this article is to discuss the process of composing this work considering its characteristics as a product resulting from the compilation of scattered documents, treated here as primary sources, which take into account contextual aspects such as patronage, editorial intentions and the processes of adaptation of the diffusion of Ignatian documents for religious, political and commercial expansion purposes, transforming an archive of restricted circulation letters into a printed work of great value to Portugal's expansionist intentions.
Keywords: Linguistic Historiography; Rhetoric; Jesuits; Japan